The Impact of Narcissism on Persuasive Messages - McQuillen, Jeffrey S.; Wald, Donna L. (Journal of Organizational Psychology, 2022)
The study examines the impact of narcissism on persuasive messages. Using scores from the NPI (Raskin & Hall, 1979), both a high and low narcissistic persuader generated a persuasive message on the topic, volunteer work. 154 student-participants evaluated these messages on a 45-item Narcissistic Language Variable Inventory (NLVI). Half of the participants evaluated the low narcissist’s message and half evaluated the high narcissist’s message. Results revealed that the message produced by the low narcissistic persuader was rated more positively than the message produced by the high narcissistic persuader. In addition, both males and females reacted more favorably to the low narcissist’s message. These results suggest that the style and content of a persuasive message is, in part, a function of the personality traits of the speaker.